PENTINGNYA KOMUNIKASI GURU DENGAN ORANG TUA DALAM MEMBANGUN KARAKTER PESERTA DIDIK - Arini, Ni Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The success of character education in schools is the success of students in building their personal character, as well as the success of teachers in building students' character. Character education will not run well if it ignores one institution, especially the family. It is because the family is an environment for the growth and development of children from early age until they become adults. Through education in the family, character of the children will be build.Communication between the school (the school principal) and parents / guardians is one realization of school accountability. Even though the teachers in the school already have the opportunity to interact and influence the lives of students, will eventually return to the lap of his parents. Some examples of communication between teachers and parents of students are: making use of teacher meetings with students' parents, utilizing technological advancements, providing school Web sites, forming school committees.Keywords: Communication, Teachers and Parents, Student Character